Ready to Serve Mackerel Curry (Goan Style) in Retortable Pouches - C.N., Ravishankar; J., Bindu; T.K., Srinivasa Gopal (Fishery Technology, 2025)
Flexible retort pouch is an ideal alternative to metal containers for heat-processed foods. Mackerel fish curry prepared in Goan style was processed and packed in indigenously developed retortable pouches having three-layer configuration of 12.5 polyester/12.5aluminium foil/ 85ja cast polypropylene. About 140g fish and 90g of curry medium were packed in retort pouch of size 17x15.5 cm. Air inside the pouch was exhausted by steam injection, heat-sealed and processed at 121.1°C to F0 values of 7, 8 & 9 minutes. Product processed to all the three F0 values were analyzed for their instrumental color, texture, shear force, commercial sterility and sensory attributes. Based on these observations, a sterilization value of 8 minutes was found to be optimum for mackerel curry with good acceptability. Processed mackerel curry in goan style was kept for storage study during which instrumental color, texture, shear force, chemical parameters like TBA, pH and sensory attributes were analysed for a period of one year at ambient temperature (28±2°C). The product remained sterile throughout the storage period. Shelf life studies showed that samples stored at ambient temperature (28±20C) had good sensory attributes and were acceptable even after a period of one year.